HISTORY IN SECONDARY EDUCATION: HISTORICAL TIME, CAUSALITY AND SOURCES - Roberto Muñoz Bolaños; Ana Rosa Lagares Gaitán (Tópicos Educacionais)
History is a field of knowledge that lacks conceptual hierarchy and where the accumulation of knowledge plays a key role in understanding the evolution of human events over time. These characteristics limit the possibilities of its teaching-learning in the school environment. In this research we have analysed the teaching of history in secondary education based on three elements: historical time, causality and historical sources. The hypothesis we have developed is that these elements constitute the fundamental basis for the teaching of history. However, they can only be developed if the historical contents studied in the classroom are previously specified, defined and limited. In order to elaborate this article we have used as fundamental sources the abundant bibliography that exists on didactics of history as well as our own teaching experience.